2015
DOI: 10.1253/circj.cj-14-1380
|View full text |Cite
|
Sign up to set email alerts
|

Does Left Atrial Appendage Morphology Influence Left Atrial Appendage Flow Velocity?

Abstract: Background:The shape of the left atrial appendage (LAA) might affect thrombus formation. The chicken wing-type LAA (CW) has been reported as unlikely to influence stroke events in atrial fibrillation (AF) patients, so we investigated whether LAA shapes could influence LAA function. Methods and Results:We studied 102 patients (64 men, age 65±9 years) who underwent transthoracic echocardiography, transesophageal echocardiography (TEE), and cardiac computed tomography prior to catheter ablation (CA) for AF. LAA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 26 publications
(19 reference statements)
4
24
0
Order By: Relevance
“…48 Furthermore, cauliflower LAA morphology was an independent predictor of stroke which is possibly related to extensive LAA trabeculations. 49 LAA flow velocity was highest among patients with chicken-wing as opposed to non-chicken wing morphology 29, 51, 52 which may explain why chicken wing morphology has the lowest risk of ischemic stroke. In addition, larger LAA orifice area has also been shown to be associated with ischemic stroke (Table).…”
Section: Left Atrial Appendage Function and Morphology In Relation Tomentioning
confidence: 95%
“…48 Furthermore, cauliflower LAA morphology was an independent predictor of stroke which is possibly related to extensive LAA trabeculations. 49 LAA flow velocity was highest among patients with chicken-wing as opposed to non-chicken wing morphology 29, 51, 52 which may explain why chicken wing morphology has the lowest risk of ischemic stroke. In addition, larger LAA orifice area has also been shown to be associated with ischemic stroke (Table).…”
Section: Left Atrial Appendage Function and Morphology In Relation Tomentioning
confidence: 95%
“…31 Furthermore, cauliflower LAA morphology was an independent predictor of stroke risk, presumably related to extensive LAA trabeculations. 32 LAA flow velocity, another inverse marker of stroke risk, was highest among patients with chicken-wing as opposed to non-chicken wing morphology, 28, 33, 34 which may also explain why chicken wing morphology has the lowest risk of ischemic stroke. In addition, larger LAA orifice area has also been shown to be associated with ischemic stroke.…”
Section: Atrial Cardiopathy: Rationale and Biological Mechanismsmentioning
confidence: 96%
“…The findings from previous studies have shown that the non-chicken wing types are associated with a greater risk of stroke than the chicken wing type, and that the highest risk is associated with the cauliflower type, even in patients with low CHADS 2 scores. However, the findings from other investigations have not demonstrated a relationship between these specific morphologies and the stroke risk [ 36 - 39 ]. A greater LAA complexity, including more extensive trabeculation and multiple lobes, has been associated with an increased stroke risk, but further studies are warranted to confirm these results.…”
Section: The Role Of the Left Atrial Appendage In Cardioembolic Strokmentioning
confidence: 97%